The Intellectual Legacy of Nuruddin Ar-Raniri and Abdurrauf As-Singkili on Hadith Studies in the Nusantara - Wagola, Zulkifli (Universitas Islam Negeri Raden Intan Lampung, 2026)
This study examines the intellectual legacy of Nuruddin Ar-Raniri and Abdurrauf As-Sinkili in shaping the tradition of hadith scholarship in seventeenth-century Nusantara. It focuses specifically on the forms, modes of presentation, and social functions of the hadith works they produced. Employing a library-based research method with descriptive-analytical and comparative approaches, the study takes Ar-Raniri's Hidayat al-Ḥabīb as well as As-Sinkili's Syarḥ Laṭīf and al-Mawa‘iẓal-Badī‘ah as its primary sources. The findings indicate that Ar-Raniri bequeathed a rigorous and systematic model of hadith codification, oriented toward the consolidation of state orthodoxy, whereas As-Sinkili offered a more flexible and adaptive mode of transmission, centered on individual spiritual formation. These methodological divergences are rooted in the distinct socio-political circumstances of Aceh that surrounded each scholar. The study thus affirms that the transmission of hadith in Nusantara was not a passive replication of Middle Eastern traditions, but rather a creative adaptation undertaken by local scholars in response to the religious needs of their society.